Pengaruh Locus Of Control dan Pelatihan Terhadap Kepuasan Kerja dengan Motivasi Kerja sebagai Variabel Intervening pada Badan Keuangan Daerah Kota Solok - Tata Santoso; Yulasmi Yulasmi; Jhon Veri (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to determine the influence of locus of control and training on job satisfaction with work motivation as an intervening variable in the Solok City Regional Finance Agency. The data analysis techniques used were multiple linear regression analysis and path analysis, by circulating 104 questionnaires and 100 returning questionnaires. The results of the study showed a positive and significant influence of locus of control on work motivation at the Solok City Regional Finance Agency. There is a positive and significant influence of training on work motivation at the Solok City Regional Finance Agency. There is a positive and significant influence of locus of control on job satisfaction at the Solok City Regional Finance Agency. There is a positive and insignificant influence of training on job satisfaction at the Solok City Regional Finance Agency. There is a positive and significant influence of work motivation on job satisfaction at the Solok City Regional Finance Agency. Motivasi kerja mampu memediasi pengaruh locus of control terhadap kepuasan kerja pada Badan Keuangan Daerah Kota Solok. Motivasi kerja mampu memediasi pengaruh pelatihan terhadap kepuasan kerja pada Badan Keuangan Daerah Kota Solok